PENGINTEGRASIAN DATA ELECTRONIC GOVERNMENT KE DALAM WEBSITE PEMERINTAH DAERAH - Triatmojo E.21111121 (PublikA, Jurnal Ilmu Administrasi Negara, 2014)
The Entitled of this article "Integrating Data Electronic Government to Local Govermnt Website”. This Article is intended to describe and analyze the Integrating Data Electronic Government to Local Govermnt Website The conclusion of this research is not maximal Integrating Data Electronic Government to Local Govermnt Website several phases. Phasing among others. The fist stage, the Phase Interpretation is socialization of the presentation information that doing each year that can be known about the progress from implementation government electronic program through the website of implementation Singkawang City Governnent. The second stage, the stage of organizing the lack of standard operating procedures on Electronic Data processing Section  Bagian Pengolah Data Elektronik Sekretariat Daerah Kota Singkawang so in doing the work can be done optimally, the human resources official who has not been charged in the Sub Division Manager of Information Systems and Software to immediately fill officials at the Sub Division of Information Systems and Software Bagian Pengolah Data Elektronik Sekretariat Daerah Kota Singkawang, management determination to continue implementing coordinated policy officer on education-related data management to ensure data submitted in accordance with Demand Bagian Pengolah Data Elektronik Sekretariat Daerah Singkawang City, Determination of Activity Schedule by time schedule has been made to the implementation of programs and activities on the Bagian Pengolah Data Elektronik Singkawang City can be accomplished predetermined. And the last , the application stage which isn good coordinate with the data management officers on education in collecting data, The application site is still only  reached the stage of published information and data download. As well as hosting on the website still ride in Pontianak Post,so when the hosting is broken or dissconect then the visitors who access the website also impaired. Keyword : Implementation    Electronic   Government  Program,  Intepretasi Data,   Organization   Website, Aplication to Program